2021
DOI: 10.1108/er-10-2020-0469
|View full text |Cite
|
Sign up to set email alerts
|

The physical, emotional and behavioral symptoms of health problems among employees before and during the COVID-19 epidemic

Abstract: PurposeThe coronavirus disease 2019 (COVID-19) epidemic has caused stress for everyone and impacted the lives of people globally. Such stress increases troubles for the employees. Therefore, the aim of the paper is to identify symptoms of health problems that employees face during the COVID-19 epidemic. Also, the aim of the paper is to examine if there are statistically significant differences in the physical, emotional and behavioral symptoms of health problems among employees before the COVID-19 epidemic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
(63 reference statements)
0
19
0
3
Order By: Relevance
“…Although researchers in the past have addressed the issue of work-family conflict, but its impact on stress level of employees during a pandemic still remains uncovered. In order to have an effective interaction of work and family dynamics with each other and fulfil high demand pressure from both the domains, people often experience fatigue, stress and anxiety issues (Ro zman and Tominc, 2021). Existing literature on the current pandemic has taken into account the direct impact of COVID-19 challenges on family disturbances (Hsu and Henke, 2020;Marimuthu and COVID-19 challenges and employees' stress Vasudevan, 2020;Alon et al, 2020) on work-life imbalance (Hj almsd ottir and Bjarnad ottir, 2020; Arora and Suri, 2020) and individual stress levels (Baert et al, 2020;Waizenegger et al, 2020;Butler and Jaffe, 2020), but neither comprehensive nor international study has been found analysing the mediating role of family-life disturbances and work-life imbalance between the relationship of COVID-19 challenges and employees' stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although researchers in the past have addressed the issue of work-family conflict, but its impact on stress level of employees during a pandemic still remains uncovered. In order to have an effective interaction of work and family dynamics with each other and fulfil high demand pressure from both the domains, people often experience fatigue, stress and anxiety issues (Ro zman and Tominc, 2021). Existing literature on the current pandemic has taken into account the direct impact of COVID-19 challenges on family disturbances (Hsu and Henke, 2020;Marimuthu and COVID-19 challenges and employees' stress Vasudevan, 2020;Alon et al, 2020) on work-life imbalance (Hj almsd ottir and Bjarnad ottir, 2020; Arora and Suri, 2020) and individual stress levels (Baert et al, 2020;Waizenegger et al, 2020;Butler and Jaffe, 2020), but neither comprehensive nor international study has been found analysing the mediating role of family-life disturbances and work-life imbalance between the relationship of COVID-19 challenges and employees' stress.…”
Section: Introductionmentioning
confidence: 99%
“…Although researchers in the past have addressed the issue of work–family conflict, but its impact on stress level of employees during a pandemic still remains uncovered. In order to have an effective interaction of work and family dynamics with each other and fulfil high demand pressure from both the domains, people often experience fatigue, stress and anxiety issues (Rožman and Tominc, 2021). Existing literature on the current pandemic has taken into account the direct impact of COVID-19 challenges on family disturbances (Hsu and Henke, 2020; Marimuthu and Vasudevan, 2020; Alon et al.…”
Section: Introductionmentioning
confidence: 99%
“…Perceived stress and impact of the social situations related to COVID-19 pandemic that may be determined by various other factors enhance the physical disorder risk such as headaches and back pain. Other study found that there was increase in physical symptoms, such as messy sleep cycle, tiredness and exhaustion, lower back pain and shoulder pain, headaches and migraines, stomach aches and indigestion among the employees during the COVID-19 epidemic (Rožman & Tominc, 2021). This finding should be the focus for further recommendation on protecting the employees' immunity and health especially farmers against COVID-19 and at the same time without sacrificing their productivity.…”
Section: Discussionmentioning
confidence: 82%
“…Em diferentes países do mundo, os sintomas emocionais relacionados ao estresse, ansiedade e depressão de profissionais atuantes em bancos têm aumentado em razão da pandemia da COVID-19. [16][17][18] Em nossa investigação, os índices de gravidade desses sintomas, também, foram elevados, corroborando com análises relativas à pandemia. Este achado pode estar relacionado ao momento de recolha dos dados, uma vez que até o medo de se infectar tem sido responsável por maiores escores de estresse, depressão e ansiedade nessa pandemia.…”
Section: Discussionunclassified